2020
DOI: 10.1123/jtpe.2018-0351
|View full text |Cite
|
Sign up to set email alerts
|

Moderate to Vigorous Physical Activity During Physical Education, Recess, and Class Time Among Elementary School Children in Qatar

Abstract: Purpose: Schools provide opportunities for children to accumulate recommended daily moderate to vigorous physical activity (MVPA). This study aimed to determine physical activity (PA) across the school day among elementary school children in Qatar. Methods: This cross-sectional study recruited 181 Grade 1 (5.8 ± 0.4 years) and Grade 4 (9.0 ± 0.5 years) children. Participants wore wrist-based accelerometers for 5 days to assess school-based PA. MVPA during physical education, recess, and class time were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
4
5
2
Order By: Relevance
“…Notably, PE classes did not demonstrate the highest percentage time in MVPA in the current study. This finding is inconsistent with the results of previous studies, which found that amongst children without disabilities [28,53,54] and children with disabilities [9,23,25], the average percentage of time spent in MVPA during PE was substantially higher than that during other school segments. Students with VI in the current study spent approximately 29.25% of PE class time engaging in MVPA and did not meet the 50% of PE time criterion [55,56].…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, PE classes did not demonstrate the highest percentage time in MVPA in the current study. This finding is inconsistent with the results of previous studies, which found that amongst children without disabilities [28,53,54] and children with disabilities [9,23,25], the average percentage of time spent in MVPA during PE was substantially higher than that during other school segments. Students with VI in the current study spent approximately 29.25% of PE class time engaging in MVPA and did not meet the 50% of PE time criterion [55,56].…”
Section: Discussioncontrasting
confidence: 99%
“…The detected gender differences stabilize in the relationship of weight status and mean PE time spent in PA and SB. In line with findings that did not determine a statistically relevant connection between BMI and PA for PE time (Meyer et al, 2013 ; Spessato et al, 2013 ; Kobel et al, 2017 ; Zimmo et al, 2020 ), our study shows a tendentially health-promoting difference for overweight and underweight girls. For both overweight and underweight girls, weight status similarly showed connections to less PE time spent in SB and more PE time spent in MVPA compared to girls with a normal weight status.…”
Section: Discussionsupporting
confidence: 92%
“…The results are in line with a previous study, which linked lower grades with significant more time in MVPA and significant less time in SB in comparison to older grades (Tanaka et al, 2018). At the same time, other studies report a significant rise of MVPA per elementary grade (Kirkham-King et al, 2017) or similar PA levels across grades (Meyer et al, 2013;Zimmo et al, 2020). The detected gender differences stabilize in the relationship of weight status and mean PE time spent in PA and SB.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations